Imaging the uptake and metabolism of glutamine in prostate tumor models using CEST MRI - Yuki Hodo; Caitlin M. Tressler; Behnaz Ghaemi; Rebecca Thomas; Aliyah S. Webster; Kirsten N. Bains Williams; Yuguo Li; Martin G. Pomper; Chi V. Dang; Zaver M. Bhujwalla; Jeff W. M. Bulte; Peter C. M. van Zijl; et al. (npj Imaging)
Abstract Glutamine metabolism is upregulated in many cancers. While multiple glutamine imaging agents have been developed and translated to clinical use, the short half-lives of their signal and instability in vivo limit the aspects of glutamine metabolism they capture. In phantoms at physiological pH, chemical exchange saturation transfer (CEST) magnetic resonance imaging (MRI) contrast was observed at 11.7 T from glutamine, downstream metabolic products (glutamate and ammonia) and their co-substrates (alanine, aspartate, and cystine/cysteine). This contrast increased at lower pH. These results suggest that both uptake and metabolism of glutamine would increase CEST signal enhancement. We then investigated the feasibility of imaging the uptake (delivery, transport and metabolism) of naturally-occuring glutamine using CEST MRI in preclinical prostate cancer models, wherein key metabolic proteins are the glutamine transporter ASCT2 and as well as enzymes GLS1, ALT2 (GPT2), AST1 (GOT1), and GDH1 (GLUD1). The LNCaP prostate cancer line exhibited higher expression of ASCT2, GDH1, ALT2, and AST1 compared to DU-145 cells. CEST MRI enhancement upon administration of glutamine was consistently higher in LNCaP 3D spheres (phantoms) and tumors (in vivo) than their DU-145 counterparts. Mass spectrometry imaging confirmed higher uptake and metabolism of glutamine in LNCaP tumors. These findings demonstrate that CEST MRI of glutamine is capable of distinguishing preclinical prostate tumor models that differ in glutamine uptake and has potential for translation to clinical use.